-2(6w-6)+6w=8+2(3w-7)

Simple and best practice solution for -2(6w-6)+6w=8+2(3w-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(6w-6)+6w=8+2(3w-7) equation:


Simplifying
-2(6w + -6) + 6w = 8 + 2(3w + -7)

Reorder the terms:
-2(-6 + 6w) + 6w = 8 + 2(3w + -7)
(-6 * -2 + 6w * -2) + 6w = 8 + 2(3w + -7)
(12 + -12w) + 6w = 8 + 2(3w + -7)

Combine like terms: -12w + 6w = -6w
12 + -6w = 8 + 2(3w + -7)

Reorder the terms:
12 + -6w = 8 + 2(-7 + 3w)
12 + -6w = 8 + (-7 * 2 + 3w * 2)
12 + -6w = 8 + (-14 + 6w)

Combine like terms: 8 + -14 = -6
12 + -6w = -6 + 6w

Solving
12 + -6w = -6 + 6w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-6w' to each side of the equation.
12 + -6w + -6w = -6 + 6w + -6w

Combine like terms: -6w + -6w = -12w
12 + -12w = -6 + 6w + -6w

Combine like terms: 6w + -6w = 0
12 + -12w = -6 + 0
12 + -12w = -6

Add '-12' to each side of the equation.
12 + -12 + -12w = -6 + -12

Combine like terms: 12 + -12 = 0
0 + -12w = -6 + -12
-12w = -6 + -12

Combine like terms: -6 + -12 = -18
-12w = -18

Divide each side by '-12'.
w = 1.5

Simplifying
w = 1.5

See similar equations:

| 18(-1x+-2)-4(-9+3x)=-14 | | 4t^2+t-60=0 | | 5y+(3y-25)=47 | | 1.3x+4.4=.07x-0.52 | | M=s-c | | -2.5(y-10)-0.166= | | -x+9-4x=-31 | | (5X^-2Y^5/4X^6Y^-3)^-2 | | -(x+4)=3 | | X+5-8x=16 | | 0.13(x+40)+0.4(x+25)=-19.25 | | 3/8k=3/2 | | 4(y+1)=-2(4y-5)+3y | | 4.7-n=4.7 | | -3k-4=k+16 | | 5x-2=x+20 | | 3x-21=o | | 20x-20x-43=43 | | -5(-8x+5)-5x=1 | | w-4+4(3w+1)=-3(w+6) | | 0.7*n=1 | | mx=3m+2x+x | | 7p=8p+1 | | 81x+15=4-48x | | 235.99c-49.99=12 | | 500x-100x=y | | 3(u-2)-9=-3(-6u+7)-u | | y-5=6x | | 2x+2(x+1)=3 | | 19x=6x | | 6y^2-7y-3= | | 2x+5x+3=17 |

Equations solver categories